Peningkatan Performa Viabilitas Benih Beberapa Varietas Padi (Oryza sativa L.) Dengan Organik Priming Ekstrak Tauge - Nove Arisandi; Raihani Wahdah; Gusti Rusmayadi (EnviroScienteae, 2020)
Quality seed is one of the determining factors of successful agricultural cultivation. Seeds that have been stored for a long time will experience seed deterioration, which is characterized by a decrease in seed viability. Improving seed viability can be done by seed invigoration. One of the seed invigoration techniques is organic priming by using organic substances extracts that are rich in phytohormones such as auxin, cytokinin, and gibberellins. The purpose of Organic priming is to improve the seed physiological and biochemical condition that related to growing speed, growing simultaneity, and germination. Mung bean sprout extract can be used as an extract for organic priming because it is proven to contain phytohormones. This study aims to determine the interaction between varieties and concentrations of bean sprout extracts and the best combination of varieties and extract concentrations on the viability of rice seeds. The research was carried out in April - June 2020 at the Laboratory of Agricultura Biology, Agriculture Faculty, Lambung Mangkurat University. The experiment  was arranged based on Factorial Randomized Block Design (RBD) 4x6 with Three replications. The variables observed were seeds germination, simultaneity of seedlings growth and speed of seedlings growth. The results showed that the interaction factor between varieties and concentration had a very significant effect on increasing seed viability and the best combination was found in Baroma varieties with concentrations of 20 % and if concentrations higher or lower than 20 % performance of rice seed viability will decrease. The highest percentage of seed germination was found in Baroma varieties with a concentration of 20 % (v4k3), which is 82.67 % not significantly different from Baroma varieties with a concentration of 10 % (v4k2) and INPARA 3 varieties with a concentration of 20 % (v1k3). The highest percentage of simultaneity of seed growth was found in Baroma varieties with a concentration of 20 % (v4k3), which is 81.50 % not significantly different from Baroma varieties with a concentration of 10 % (v4k2), Mutant line No. 14 with a concentration of 20 % (v3k3), and INPARA 3 variety with a concentration of 20 % (v1k3), while the fastest percentage of seed growth rate is in Baroma with a concentration of 20 % (v4k3), which is 29.50% significantly different from all varieties and other bean sprout extract concentrations.